The incremental commitment spiral model : principles and practices for successful systems and software - Boehm, Barry (Addison Wesley, 2014)
"The title makes a huge promise: a way to divide commitment into increments that are both meetable (good news for developers) and meaningful (good news for managers and stakeholders). And the book makes good on that promise."--Tom DeMarco, Principal, The Atlantic Systems Guild, author of Peopleware, Deadline, and Slack "I am seriously impressed with this ICSM book. Besides being conceptually sound, I was amazed by the sheer number of clear and concise characterizations of issues, relationships, and solutions. I wanted to take a yellow highlighter to it until I realized I'd be highlighting most of the book." -Curt Hibbs, Chief Agile Evangelist, Boeing Use the ICSM to Generate and Evolve Your Life-Cycle Process Assets to Best Fit Your Organization's Diverse and Changing Needs Many systems development practitioners find traditional "one-size-fits-all" processes inadequate for the growing complexity, diversity, dynamism, and assurance needs of their products and services. The Incremental Commitment Spiral Model (ICSM) responds with a principle- and risk-based framework for defining and evolving your project and corporate process assets, avoiding pitfalls and disruption, and leveraging opportunities to increase value. This book explains ICSM's framework of decision criteria and principles, and shows how to apply them through relevant examples. It demonstrates ICSM's potential for reducing rework and technical debt, improving maintainability, handling emergent requirements, and raising assurance levels. Its coverage includes What makes a system development successful ICSM's goals, principles, and usage as a process-generation framework Creating and evolving processes to match your risks and opportunities Integrating your current practices and adopting ICSM concepts incrementally, focusing on your greatest needs and opportunities About the Website: Download the evolving ICSM guidelines, subprocesses, templates, tools, white papers, and academic support resources at csse.usc.edu/ICSM